Protective and decorative coatings : manufacture and uses, colloids, oleoresinous vehicles and paints, water and emulsion paints, lacquers, printing inks, luminescent paints, and stains - Mattiello, Joseph J. (Wiley)
Contiene: Colloids; Oleoresinous vehicles; Oleoresinous paints; Water and emulsion paints; Lacquers; Printing inks; Luminescent coating; Paint manufacturing procedure; Stains.